Function-Spacer-Lipid (FSL) constructs enable inkjet printing of blood group antigens - Barr, K; Diegel, O; Parker, S; Bovin, N; Henry, S (John Wiley & Sons Ltd, 2010)
A limitation of inkjet printing antigens to solid surfaces is that the molecule to be printed must be dispersible in solution, retain antigenicity, and remain on the printed surface when exposed to biological solutions. FSL (function-spacer-lipid) constructs were designed to be dispersible in water and to attach a range of synthetic molecules to cell membranes. FSL constructs currently include carbohydrates, peptides, fluorophores, ligands and biotin and are being used in the manufacture of modified cells called ‘‘kodecytes’’ for use in blood group typing laboratories and for research purposes (1–2). FSL constructs have now been used to create prototype diagnostic assay kits, using standard desktop inkjet printers, by simply replacing the ink in a spent cartridge with a solution of FSL construct. The FSL constructs can then be printed onto a substrate in much the same way one might print a letter or drawing on a sheet of paper. Blood group FSLs have been printed onto silica and nitrocellulose surfaces, and used to identify blood group antibodies in diagnostic and research samples. Combining FSL technology with existing inkjet printing technology provides a cost effective alternative to existing methods of manufacturing diagnostic test kits, including microarrays which, for the most part, use robotics. In addition to cost savings the versatility of this manufacturing method provides additional benefits for research laboratories and micro-analyses. Acknowledgement: Supported by KODE Biotech Ltd (kodebiotech.com)